Preformed Stainless-Steel Crowns: Their Effects on Oral Hygiene Maintenance and Gingival Health - A Prospective Original Research - Alharbi Majed; Habibullah Mohammed Ali; Almulhim Basim; Alharthi Naji; Ravi Prakash Sasankoti Mohan; Ahmad Muhammad Zubair (Wolters Kluwer Medknow Publications, 2024)
The stainless-steel crown (SSC) is a durable restoration and has several indications for use in primary teeth such as following a pulpotomy/pulpectomy, fractured teeth, teeth with developmental defects, or large multi-surface caries lesions where amalgam is likely to fail. Due to its durability and a lifespan like the primary tooth, it could well be the gold standard in restorative care. SSCs protect the crown from fracture, reduce the possibility for leakage, and ensure a biological seal. However, the placement of the SSC should follow a meticulous technique. There are some clinical situations where the SSC may fail, leading to plaque accumulation and gingivitis. This could be secondary to improper crimping of crown margins, which lead to poorly adapted SSC. In some clinical situations, ledge formation under the crown or failure to clean excess cement can contact the gingiva and cause gingival inflammation. This study was carried out on 41 children between the ages of 4 and 10 in Al Qassim region to study the effects of SSCs on gingiva and oral hygiene. The study also aims to establish the correlation between SSC adaptation and post-insertion inflammation. The plaque and gingival index were recorded at 3 months' post SSC insertion. Clinical examination was undertaken, and gingival index (Loe and Silness 1967) and plaque index (Silness and Loe 1967) were used to record gingival health and plaque accumulation, respectively. The result for post-inflammation and SSC adaptation showed that there was no statistically significant difference in post-insertion inflammation and crown adaptation (P value = 0.216). The result for pre-operative inflammation and post-operative inflammation shows that there is no significant difference in post-inflammation and adaptation (P value = 0.47). We found that oral hygiene care had a heightening effect and oral hygiene maintenance plays a key role in preventing gingival inflammation irrespective of the SSC adaptation over short periods of time (3 months).